2013
DOI: 10.1109/tns.2013.2257183
|View full text |Cite
|
Sign up to set email alerts
|

Generalization Evaluation of Machine Learning Numerical Observers for Image Quality Assessment

Abstract: In this paper, we present two new numerical observers (NO) based on machine learning for image quality assessment. The proposed NOs aim to predict human observer performance in a cardiac perfusion-defect detection task for single-photon emission computed tomography (SPECT) images. Human observer (HumO) studies are now considered to be the gold standard for task-based evaluation of medical images. However such studies are impractical for use in early stages of development for imaging devices and algorithms, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…10,11 Therefore, anthropomorphic model observers (MO) that perform as humans in specific clinical tasks were introduced and are now widely used in the CT research community for the development and optimization of imaging devices and reconstruction algorithms. 12,13 In recent years, machine learning approaches like support vector machines (SVM), [14][15][16][17] relevance vector machines (RVM) [18][19][20] and neural networks, 17 were introduced to build anthropomorphic model observers for task-based image quality assessment of single photon emission computed tomography (SPECT). The authors observed better agreements with human observers of these methods compared to the widely used channelized Hotelling observer (CHO).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Therefore, anthropomorphic model observers (MO) that perform as humans in specific clinical tasks were introduced and are now widely used in the CT research community for the development and optimization of imaging devices and reconstruction algorithms. 12,13 In recent years, machine learning approaches like support vector machines (SVM), [14][15][16][17] relevance vector machines (RVM) [18][19][20] and neural networks, 17 were introduced to build anthropomorphic model observers for task-based image quality assessment of single photon emission computed tomography (SPECT). The authors observed better agreements with human observers of these methods compared to the widely used channelized Hotelling observer (CHO).…”
Section: Introductionmentioning
confidence: 99%
“…RSFM is potentially more capable than JCFO since in RSFM the kernel width parameter is not used for feature selection and so can be employed for improving the performance. Furthermore, multikernel methods [15] are shown to improve the classification performance for example in RVM. RSFM is capable of employing multikernel methods and we are currently extending the proposed RSFM to a multikernel one.…”
Section: A Discussionmentioning
confidence: 99%
“…The numerator of (17) can be calculated by using (12), (14), and (15). The denominator of (17) is the integral of the numerator with respect to variables w and λ.…”
Section: B Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…(2) It allows for partial area under ROC curve analysis, 13 which may have better clinical relevance for a specific level of sensitivity and/or specificity. (3) In our current research on model observer development using a machine learning methodology, 6,[14][15][16] we observed that models perform better if trained on a human confidence rating.…”
Section: Introductionmentioning
confidence: 89%